Differences in Students' Conceptual Understanding with the Problem-based Learning Model Through a Scientific Approach at Grade V Elementary School Students - Siska Jamina Hia, Marta; Virdinarti Putra, Lisa (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study presents the impact of the Problem-based Learning model on the conceptual understanding of V-grade students at SD Negeri Karangjati 04 through a scientific approach. The research adopts a quantitative method with a Quasi-Experimental Design (Non-Equivalent Control Group Design). The population comprises all students of SD Negeri Karangjati 04. The sample consists of class VA as the Experimental group and class VB as the Control group. Data collection techniques included tests using pre-tests and post-tests, as well as non-test methods such as observation, questionnaires, documentation, and unstructured interviews. Data analysis involved normality, homogeneity, and independent sample t-tests. The findings indicate that implementing problem-based learning models with a scientific approach can enhance students’ conceptual understanding, as demonstrated by the independent sample t-test, which shows a significant value of 0.000 < 0.05 and the simple linear regression test, indicating a significant value of 0.009 < 0.05. Based on these results, it can be concluded that the use of problem-based learning models with a scientific approach can improve students' ability to comprehend concepts.